Проблема відновлення давньоруських укріплень Старокиївської гори в середині XVII ст. - Жигола, В.С. (Археологія, 2017)
Статтю присвячено дослідженню писемних, графічних і археологічних джерел щодо фортифікаційних споруд Старокиївської гори Х—ХІІІ та XVII—XVIIІ ст. Атрибутуються ділянки, де мало місце відновлення давньоруських укріплень і ділянки, де було зведено нові вали та рови середини XVII ст. Archaeological research of the fortifications at Starokyivska Mountain present a series of cases where two parallel or almost parallel rows of moats and embankments are recorded. A smaller moat with abrupt sides and a wide moat with rounded bottom and big circumferences situated outside the smaller moat are recorded in all cases. No scholar questioned the first moat’s dating by the Ancient Rus period, while the outer moat was dated in different ways: by the Ancient Rus period, by the modern period, or being used in both periods. To the author’s opinion, the outer moat belonged only to the modern era, though it cannot be excluded that an older moat, re-built and widened, could lay on its way in certain places. Existing of two parallel moats dated by different stretches testify that part of Ancient Rus moats were filled in and part of embankments was dismounted by the period from 1650s to 1670s; therefore, the Starokyivska fortress’ builders dug a new moat and raised a new embankment. Besides, the modern period fortification’s perimeter is bigger than the Ancient Rus one; this is caused by an attempt to fully use the natural conditions of Starokyivska Mountain, as well as to create the fortifications corresponding the up-to-date military norms: straight wall sections with sharp turns. Places where the Ancient Rus and the modern periods fortification lines coincide are recorded. These are the places where the conditions at Starokyivska Mountain are used to the limit both in the period from the 10th to the 13th centuries, and in the 17th century. It was also decided in the modern period to use favourably designed Golden and the Liadski Gates. The comparison of 1750 plan of Kyiv with today city plan and the usage of archaeological research data allowed the author to clarify the places where the 10th century, the 11th—13th, and the 17th and 18th centuries fortification structures were built. It will be useful in future research of various periods fortifications in Upper Kyiv. Археологические исследования укреплений Старокиевской горы предоставляют ряд случаев из зафиксированными двумя параллельными или почти параллельными рядами рвов и валов. Во всех случаях зафиксировано меньший ров с резкими склонами стен и широкий округлодонный ров, который имеет большую окружность и расположен с внешней стороны меньшего рва. Датировка первого рва древнерусским временем не вызывает сомнений ни у кого из исследователей, внешний же датировался по-разному — древнерусским временем, Новым временем или бывшим в употреблении в оба периода. По нашему мнению, внешний ров принадлежит только к периоду Нового времени, хотя и не исключено, что в некоторых местах мог проходить ров древнее, который был восстановлен и увеличен. Существование двух параллельных рвов различных временных отрезков свидетельствует о том, что на 50— 70-е гг. XVII в. часть древнерусских рвов была засыпана, часть валов была демонтирована, поэтому строители Старокиевской крепости прокапывают новый ров и насыпают новый вал. Кроме того, периметр фортификации Нового времени больше древнерусского, что объясняется попыткой полностью использовать природные условия Старокиевской горы, а также создать укрепления, которые отвечали тогдашним военным нормам — прямые отрезки стен с резкими поворотами. Отмечены места совпадения линий укреплений древнерусского и Нового времени — это места, где максимально использованы условия Старокиевской горы как в Х—ХIII вв., так и в XVII в. Также в Новое время было решено использовать выгодно устроенные Золотые и Лядские ворота. Сопоставления плана Киева 1750 г. с современнымпланомгорода, использование данных археологических исследований позволили уточнить места устройства фортификационных сооружений Х, ХI—ХIII и ХVII—XVIII вв., что пригодится при будущих исследованиях укреплений Верхнего Киева разных периодов.